The neurointerventional procedure room of the future: predicting likely innovations in design and function. (10th January 2011) - Norbash, Alexander; Klein, Lloyd W; Goldstein, James; Haines, David; Balter, Stephen; Fairobent, Lynne; Miller, Donald L
Abstract : The Multispecialty Occupational Health Group, as part of their work, have considered likely characteristics of the neurointerventional surgery operating room of tomorrow. Such rooms will be distinguished by certain architectural features and markedly increased information technology features. The novel architectural features will include system proximities, such as embedding the procedure room next to traditional operating rooms, anesthesia recovery units, intensive care units or the emergency department. Novel features will likely also include distinct, contained, open sided control areas for technical and medical staff, integrated modular multimodality capability for non-ionizing extravascular and endovascular imaging and therapeutic tools, and various additional described distinct features. Information technology features will permit importation of multiple imaging datastreams, quality and performance monitoring, measuring and exportation, and utilization trajectory matched automated inventory systems. Additional needs will likely include streaming imaging and physiologic information channels, in selected instances supplemental cross sectional and metabolic imaging equipment, robotic intermediaries and more formally designated stations for datastream and scrub technologists.